The multi‐step process optimisation of candied kidney beans with high nutrients and γ‐aminobutyric acid retention. (19th November 2022) - Xiao, Tianzhen; Wang, Zhonglei; Ma, Yuling; Wang, Aixia; Chen, Zhiying; Wang, Lili; Wang, Fengzhong; Tong, Li‐Tao
Summary: The candied kidney bean contains a vital bioactive compound called γ‐aminobutyric acid (GABA), which could be easily lost in the traditional producing processes like soaking, cooking and candying. The traditional procedure distinctly decreased the GABA content to the GABA retention rate of 34.01% in the candied kidney bean. In this study, the optimum technological methods of soaking, cooking and candying were determined by single factor experiment according to the GABA content. The optimised producing condition was that the kidney bean was soaked at 55°C for 5 h, followed by atmospheric steaming for 35 min and then subjected to microwaving candying at 150 W for 25 min. By the optimal procedure, the GABA content retention reached 75.33%. Meanwhile, the texture, nutrient contents and antioxidant capacity were obviously improved in the candied kidney beans produced by the optimal methods. Abstract : The procedure optimization of candied kidney bean with high GABA retention.